Mapping citizenship in India - Roy, Anupama (New Delhi ; Oxford : Oxford University Press, 2010)
This study traces the Citizenship Act of India, 1955 - from its inception, through various amendments (1986, 2003, and 2005), its connection with other significant laws such as the Abducted Persons Recovery and Rehabilitation Act (1949) and the Illegal Migrants Determination by Tribunals Act (1983), and relevant judgments - to see how citizenship unfolded among differentially located individuals, communities, and groups.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Citizenship -- India